The usage of motion graphics in promotional videos: a case study for digital technology hub/ Shahmi Hambali Shahrulnizam ... [et al.] - Shahrulnizam, Shahmi Hambali; Che Din, Sharkawi; Mohd Lazim, Nur Aniza; Mohamed Ghazali, Nabila Aimi (Universiti Teknologi MARA, Perak, 2023)
The effectiveness of promotional videos in visually conveying a brand's message to consumers has been widely recognized. A qualitative research method was employed to explore this phenomenon further, utilising content analysis of promotional videos from smartphone manufacturers. The specific focus of the study was to examine the usage of motion graphics in promotional videos for digital technology hubs. The research findings revealed that incorporating various motion graphics techniques, such as eases, anticipation, timing, spacing, and rhythm, was highly successful in spreading brand messages related to digital technology hubs. By leveraging these techniques, brands could effectively communicate their key messages and promote their digital technology offerings.